Analisis Keselamatan dan Kesehatan Kerja (K3) Menggunakan Metode Hazop Studi Kasus: Departemen Teknik PT Sinde Multikemasindo - Zakaria, Ahmad; Arifin, Jauhari; Nugraha , Billy (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT Sinde Multi Kemasindo is a plastic packaging industry company located in Tambun, West Java. PT Sinde Multi Kemasindo produces products in the form of preforms, 200 Ml bottles, 350 Ml bottles, 500 Ml bottles and screw caps with 2 colors, namely green and blue.  PT Sinde Multikemasindo carries out the production process based on orders or direct requests from consumers.  Based on the data obtained, from January to November 2023, there were 31 cases of work-related accidents in the engineering department of PT Sinde Multikemasindo, with a description of extreme risk of 0%, high risk of 23%, moderate risk of 61%, and low risk of 16%. with the classification of moderate and mild accidents. In an effort to minimize work accidents, work accident analysis can be carried out using the Hazard and Operability Study (HAZOP) method and fisbon approach The results found 31 hazards in the engineering department and can be categorized into 31 hazard sources. From the risk level assessment results, there are 0 sources of hazard classified as extreme, 73 sources of hazard classified as high risk, 19 sources of hazard classified as medium risk, and 5 sources of hazard classified as low risk. This study provides recommendations for improvement in the form of conducting inspections to workers, providing signs or posters regarding the use and need for PPE, conducting supervision (punishment and reward system), prohibiting entry into the production work area without using PPE and conducting medical examinations on workers exposed to dust.